2008
DOI: 10.1093/jmedent/45.6.1187
|View full text |Cite
|
Sign up to set email alerts
|

Culex Flavivirus Isolates from Mosquitoes in Guatemala

Abstract: A new strain of Culex flavivirus (family Flaviviridae, genus Flavivirus, CxFV), an insect virus first described in Japan, was isolated from adult Culex quinquefasciatus Say (Diptera: Culicidae) collected in 2006 from Izabal Department on the Caribbean coast of Guatemala. Mosquito pools were assayed for flavivirus RNA by using flavivirus group-specific primers that amplified a 720-bp region of the nonstructural (NS) 5 gene by standard reverse transcriptase-polymerase chain reaction. From 210 pools (1,699 mosqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 8 publications
2
55
0
4
Order By: Relevance
“…It was the first ''insect flavivirus'' (e.g viruses that propagate only in mosquito cells but not in mammalian cells) discovered. To date, six other ''insect flaviviruses'' have been described: Kamiti River virus (KRV), isolated from field collected Aedes macintoshi in Africa in 2003 (Crabtree et al 2003); Culex Flavivirus (CxFV), isolated mainly from Culex mosquitoes in Japan, Indonesia (Hoshino et al 2007), Guatemala (Morales-Betoulle et al 2008), México (Farfan-Ale et al 2009), United States, Trinidad (Kim et al 2009), and Uganda (Cook et al 2009); Aedes Flavivirus (AEFV), isolated from Aedes albopictus mosquito in Japan (Hoshino et al 2009); Quang Binh virus (QBV) isolated from Culex tritaeniorhynchus in Vietnam (Crabtree et al 2009); Nakiwogo virus (NAKV) isolated from Mansonia africana nigerrima in Uganda (Cook et al 2009); and Calbertado virus detected mainly in Cx. tarsalis mosquitoes in Canada (Pabbaraju et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was the first ''insect flavivirus'' (e.g viruses that propagate only in mosquito cells but not in mammalian cells) discovered. To date, six other ''insect flaviviruses'' have been described: Kamiti River virus (KRV), isolated from field collected Aedes macintoshi in Africa in 2003 (Crabtree et al 2003); Culex Flavivirus (CxFV), isolated mainly from Culex mosquitoes in Japan, Indonesia (Hoshino et al 2007), Guatemala (Morales-Betoulle et al 2008), México (Farfan-Ale et al 2009), United States, Trinidad (Kim et al 2009), and Uganda (Cook et al 2009); Aedes Flavivirus (AEFV), isolated from Aedes albopictus mosquito in Japan (Hoshino et al 2009); Quang Binh virus (QBV) isolated from Culex tritaeniorhynchus in Vietnam (Crabtree et al 2009); Nakiwogo virus (NAKV) isolated from Mansonia africana nigerrima in Uganda (Cook et al 2009); and Calbertado virus detected mainly in Cx. tarsalis mosquitoes in Canada (Pabbaraju et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CxFV was first isolated from Culex pipiens Linnaeus mosquitoes in Japan (Hoshino et al 2007) but appears to have a global distribution, with additional variants identified in other Culex species and subspecies from Mexico, Uganda, Trinidad, and the United States (Morales-Betoulle et al 2008, Blitvich et al 2009, Cook et al 2009, Farfan-Ale et al 2009, Kim et al 2009). The insect-specific designation of CxFV derives from the observation that it has been cultured in the laboratory only in mosquito cell lines and, additionally, that it has been identified in many natural populations of Culex mosquitoes (Hoshino et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…mosquitoes 5 and has since been described in Culex spp. mosquitoes from Guatemala, 12 Mexico, 13 Trinidad, 14 Texas, 14 Iowa, 15 and Uganda. 10 Quang Binh virus was isolated from Cx.…”
Section: Introductionmentioning
confidence: 99%